A financial approach to renewable energy production in Greece using goal programming. (August 2017) - Zografidou, Eleni; Petridis, Konstantinos; Petridis, Nikolaos E.; Arabatzis, Garyfallos
Abstract: Investing in renewable energy production is a high interest venture considering global energy needs and the environmental impact of fossil fuel consumption. Motivated by the goals set by the European Union towards 2020, this study aims at designing a renewable energy map (installing solar power plants) in Greece. Three aspects are considered, namely, social, financial, and power production aspects. A goal programming model is developed under target and structural constraints, and all possible weight combinations are examined. The solutions derived from each iteration are subjected to a financial meta-analysis, considering different tax and return scenarios aligned to the Greek taxation and banking system. The analysis considers Greece and each region separately, taking net present value (NPV) as an objective measure to assess the solutions. From the results, it is concluded that the internal rate of return is approximately 22.5 % − 25 % for the overall network. In addition, higher NPV values are obtained when the financial and power production aspects are given greater emphasis. The proposed model provides multi-dimensional information for decision makers; investors can determine the optimal budgeting mix, and policy makers can determine the weight on each aspect that guarantees the success of the venture. Highlights: A Goal Programming model for installing solar power plants in Greece is proposed. Social, Financial, Power production aspects are assumed. Financial meta analysis is conducted using NPV. IRR is approximately 22.5%–25% for all regions.